Publishing in the organizational sciences - Cummings, L.L.; Frost, Peter J. (Thousand Oaks Sage Publications, 1995)
This comprehensive overview of all aspects of the publishing process has been written especially for prospective authors who want to learn more about the field to advance their careers and publishing success. More than just a `how to' book, this volume explains the entire context of scholarly publishing and how it should, ideally, work toward advancing knowledge and successful management practice.